One-Pot Synthesis of Indolo[2,3-c]quinolin-6-ones by Sequential Photocyclizations of 3-(2-Azidophenyl)-N-phenylacrylamides - Li, Zhanshan; Wang, Weixia; Zhang, Xiaotian; Hu, Congcong; Zhang, Wei (Synlett, 2013)
A one-pot synthesis of indolo[2,3-c]quinolin-6(7H)-ones was achieved by sequential photocyclizations of 3-(2-azidophenyl)-N-phenylacrylamides in moderate to high yields. The reactions proceeded via photochemical cyclization of aryl azides to form N-phenylindol-2-carbamides and subsequent 6π-electrocyclic reaction and oxidative aromatization to afford the corresponding indolo[2,3-c]quinolin-6(7H)-ones.
Keywords: indolo[2,3-c]quinolin-6(7H)-ones; photocyclization; 3-(2-azidophenyl)-N-phenylacrylamides; aryl azides; 6π-electrocyclic reaction